MELODICAL AND HARMONIC ANALYSIS OF CHURCH AND FOLK HYMNS FROM COLLECTION „OCTOICH“ St. St. MOKRANJAC AND THE POSSIBILITY OF THEIR APPLICATION IN THE SOLFEGGIO TEACHING (Heritage, 2024)
The basic research direction in this work refers to the analysis of all compositions from the collection of church-folk chants „Octoich“ compiled by Stevan Stojanović Mokranjac, with the aim of solving certain problems in the field of solfeggio teaching with the help of folk church chants. Considering that spiritual music is very present around us today (at church services, concerts, school performances, etc.), we believe that its inclusion in music teaching in music schools would significantly contribute to its preservation. During the research, all compositions from the collection (320 of them) were processed, and for analysis we selected the songs „Na hvaliteh“ and „Stihovne stihire“ as the most complete compositions from the melodic-harmonic and formal aspect. In the results of the analysis, there are concrete proposals for work in the solfeggio teaching considering age and teaching areas.
Keywords: solfeggio, Octoich, Mokranjac, melodic-harmonic analysis, church-folk chants